Antifungal activity of cinnamaldehyde against Aspergillus fumigatus involves disruption of the TCA cycle and protein metabolism - Li, Fang; Cheng, Xi; Li, Ling; Jiang, Jinglu; Liu, Yan; Mo, Siyu; Jiang, Wenxia; Liu, Li; Baldi, Salem; Long, Nanbiao (Frontiers in Microbiology, 2025)
Aspergillus fumigatus is an environmental opportunistic fungal pathogen, which can lead to invasive aspergillosis in immunocompromised individuals, and resistant to conventional antifungual agents has become a growing concern. This study investigated the antifungal activity and the molecular antifungal mechanisms of Cinnamaldehyde (CA) against A. fumigatus, specifically its impact on metabolic pathways and protein metabolism. In susceptibility tests, CA was found to exhibit promising antifungal activity against A. fumigatus in both solid and liquid culture (biomass) systems, with the minimum inhibitory concentration (MIC) determined as 40–80 μg/mL. Quantitative spore viability assays under elevated CA concentrations demonstrated that the antifungal efficacy of CA against A. fumigatus is primarily attributable to its direct fungicidal mechanism. Interestingly, CA also showed equivalent antifungal activity against itraconazole- resistant strains R1 (ITZ, MIC 8 μg/mL) and R2 (ITZ, MIC 8 μg/mL), as it did against its parental strain Af293 (ITZ, MIC 1.5 μg/mL), suggesting its potential value to overcome resistance mechanisms associated with conventional antifungal therapies. Further proteomics and metabolomics analyses revealed that CA significantly affected the tricarboxylic acid (TCA) cycle and protein metabolism, with 167 differentially expressed proteins and 350 altered metabolites identified after 180 min of treatment (FC > 2 or <0.5, p < 0.05, VIP > 1). Following treatment with CA, the protein expression of the putative translation initiation factor eIF4E3 (AFUB_051690), the putative leucyl-tRNA synthetase LeuRS (AFUB_093380), prolyl-tRNA synthetase ProRS (AFUB_010170) and the putative peptidyl-tRNA hydrolase Pth1 (AFUB_053480) exhibited a significant decrease. Moreover, deletion of pth1 resulted in a severe growth defect and hypersensitivity to CA, as evidenced by complete growth arrest at 30 and 45 μg/mL CA. Altogether, the results uncovered a novel antifungal mechanism of CA against A. fumigatus and suggest that CA or its derivatives could be developed as effective antifungal drugs.